(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In recent years, the multidisciplinary field of human-computer interaction has emerged as anexciting new area for study. The use of human-computer interaction to construction safety managementhas increased throughout the fourth industrial revolution, which has considerably aided the developmentof hazard detection in the construction sector. However, only a small number of researchers havethoroughly examined how human-computer interaction has evolved in the detection of building hazards.In this study, ACM Digital Library, Web of Science, Google Scholar, and Scopus were used to assess 274relevant publications published between 2000 and 2021 in the field of human-computer interaction inconstruction hazard detection (CHR-HCI). Human-computer interaction has had a substantial impact ondanger detection during the last two decades, according to the research. In addition, a number of newresearch areas have been created as a result of this work, Experiments that include multimodalphysiological data analysis, intuitive gadgets and sensors as well as the development of a humancomputerinterface safety management platform using big data are all included in this project. Virtualreality, ergonomics, computer vision, and computer simulation will be the emphasis of future researchmodules. In this work, we constructed a theoretical map that reflected the findings of previous studiesand their connections, and for the future development of human-computer interaction in the field ofthreat detection, we gave guidance.